STRATEGI GERAKAN KELOMPOK KEPENTINGAN DALAM PENGAWASAN PENGENDALIAN PEMANFAATAN RUANG KAWASAN BANDUNG UTARA - Sagita, Novie Indrawati (Departemen Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2016)
North Bandung area (KBU) is designated as a conservation area to protect the natural environment for the activities of life and urban development in the surrounding region. KBU become a magnet of the owners of capital to invest in the region to build a residential and tourism facilities. Development in KBU has acquired resistance from interest groups as deemed to have caused environmental damage and socio-economic impact to the surrounding community. Development in KBU clearly violate local regulations No. 1 of 2008, where every building permit (IMB) issued by the district/city must have a recommendation from the governor, but the deviations of licensing as a collusion of the government of officials and the owners of capital continue. This research method using descriptive qualitative approach, which describes and analyzes the licensing irregularities in the construction of KBU. The results showed that the strategy of interest groups have not been effective in pressuring the government to stop granting licenses and prevent development in KBU. Movement of the interest groups need to be winning support through the formation of opinion in a way to build public awareness about the impact of environmental degradation as a result of development at KBU. Opinion formation is considered to be more effective when these efforts were supported by the help of the mass media in disseminating the opinion.